A sodium fluoride sensitive mutant of Aspergillus nidulans - S. G. Shawcross; B. M. Baker; P. Strike; B. M. Faulkner (Fungal Genetics Reports, 1994)
Fluoride is a widely spread naturally occurring substance in many foods and is used extensively for industrial purposes. The addition of fluoride to drinking water has been assumed to be safe. However, a number of studies have indicated that sodium fluoride is both genotoxic and cytotoxic to mammalian cells (Tsutsui et al. 1984 Mut. Res. 139:193-198). There is conflicting evidence suggesting that NaF is not genotoxic (Kram et al. 1978 Mut. Res. 57:51-55; Martin et al. 1979 Mut. Res. 66:159-167; Li et al. 1987 Mut. Res. 192:191-202) and can suppress the activity of polyfunctional alkylating agents (Obe and Slacik-Erben 1973 Mut. Res. 18:369-371).